On the polarization characteristics of Cherenkov radiation from a dielectric screen; JETP Letters; Vol. 105, iss. 4 - Konkov (Kon'kov) A. S. Anatoliy Sergeevich; Potylitsyn A. P. Alexander Petrovich; Shevelev M. V. Mihail Viktorovich; Aryshev A. S. Aleksandr Sergeevich (2017, 2017)
Title screen